Study on the Control of Dichloroacetonitrile Generation by Two-Point Influent Activated Carbon-Quartz Sand Biofilter - Xinrui Gui; Huining Zhang; Bixiao Ji; Jianqing Ma; Meijuan Xu; Yan Li; Ming Yan (Membranes, 2022)
Aiming at the problem of highly toxic Nitrogenous disinfection by-products (N-DBPs) produced by disinfection in the process of drinking water, two-point influent activated carbon-quartz sand biofilter, activated carbon-quartz sand biofilter, and quartz sand biofilter are selected. This study takes typical N-DBPs Dichloroacetonitrile (DCAN) as the research object and aromatic amino acid Tyrosine (Tyr), an important precursor of DCAN, as the model precursor. By measuring the changes of conventional pollutants in different biofilters, and the changes of Tyr, the output DCAN formation potential of the biofilters, this article investigates the control of DCAN generation of the two-point influent activated carbon-quartz sand biofilter. The results show that the average Tyr removal rate of the three biofilters during steady operation is 73%, 50%, and 20%, respectively, while the average effluent DCAN generation potential removal rate is 78%, 52%, and 23%, respectively. The two-point influent activated carbon-sand biofilter features the highest removal rate. The two-point water intake improves the hypoxia problem of the lower filter material of the activated carbon-quartz sand biofilter, and at the same time, the soluble microbial products produced by microbial metabolism can be reduced by an appropriate carbon sand ratio, which is better than traditional quartz sand filters and activated carbon-quartz sand biofilters in the performance of controlling the precursors of N-DBPs.